1964
DOI: 10.1161/01.cir.30.6.830
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Effects of Pargyline in Hypertensive Patients

Abstract: Pargyline exerts its antihypertensive effect via a predominant reduction in peripheral vascular resistance, whereas cardiac output is not altered significantly. The effect on renal blood flow is inconsistent, but a significant reduction in glomerular filtration rate does occur. Therefore the drug should be used with appropriate caution in patients with significant impairment of renal function. The hemodynamic response observed with pargyline is similar to that obtained with other MAO inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1966
1966
1988
1988

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Oral treatment with debrisoquine has been reported to cause little change in renal plasma-flow and glomerular filtration rate (Abrams et al, 1964), although Onesti et al (1964) state that cardiac output, renal blood-flow, and glomerular filtration rates were decreased. Though we have not made any measurements of this kind, none of our patients showed any evidence of renal or cardiac deterioration which could be attributed to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Oral treatment with debrisoquine has been reported to cause little change in renal plasma-flow and glomerular filtration rate (Abrams et al, 1964), although Onesti et al (1964) state that cardiac output, renal blood-flow, and glomerular filtration rates were decreased. Though we have not made any measurements of this kind, none of our patients showed any evidence of renal or cardiac deterioration which could be attributed to the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Pargyline and a-methyldopa also produce a further blood pressure reduction in an upright position, but the effect does not appear to be related to venous pooling. With both drugs the cardiac output is maintained at normal levels in the erect position, while the increase in peripheral resistance is abolished (91,(93)(94)(95)(98)(99)(100).…”
Section: Herrlodynamics Of Hypertensionmentioning
confidence: 99%
“…Changes in regional flow are minimal with agents which have little or no effect on cardiac output. With respect to the renal circulation, there is little change in flow with «-methyldopa (93,97) and protoveratrine (66), while pargyline (99,100) and chlorothiazide (114) produce a slight decrease in flow.…”
Section: Herrlodynamics Of Hypertensionmentioning
confidence: 99%
“…I It has been established that methyldopa is capable of reducing the blood-pressure when given orally (Brest et al, 1961 ;Irvine et al, 1962;Onesti et al, 1962) or intravenously (Wilson et al, 1961;Gillespie et al, 1962). Sannerstedt et al (1962) found after oral methyldopa that the rises of blood-pressure induced by exercise were smaller.…”
Section: Belief In Individual Worthmentioning
confidence: 99%